How do you solve #3(3x+1)-(x-1)=6(x+10)#?
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation 3(3x + 1) - (x - 1) = 6(x + 10), first distribute the terms inside the parentheses, then combine like terms, and finally isolate the variable on one side of the equation. Here are the steps:
-
Distribute the terms: 9x + 3 - x + 1 = 6x + 60
-
Combine like terms: 9x - x + 3 + 1 = 6x + 60 8x + 4 = 6x + 60
-
Subtract 6x from both sides: 8x - 6x + 4 = 6x - 6x + 60 2x + 4 = 60
-
Subtract 4 from both sides: 2x + 4 - 4 = 60 - 4 2x = 56
-
Divide both sides by 2: 2x / 2 = 56 / 2 x = 28
Therefore, the solution to the equation is x = 28.
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7